Glioblastoma Multiforme and Genetic Mutations: The Issue Is Not Over Yet. An Overview of the Current Literature - Montemurro, Nicola (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Objective Glioblastoma multiforme (GBM) is still a deadly disease with a poor prognosis and high mortality, despite the discovery of new biomarkers and new innovative targeted therapies. The role of genetic mutations in GBM is still not at all clear; however, molecular markers are an integral part of tumor assessment in modern neuro-oncology.Material and Methods We performed a Medline search for the key words “glioblastoma,” “glioblastoma multiforme,” and “genetic” or “genetics” from 1990 to the present, finding an exponential increase in the number of published articles, especially in the past 7 years.Results The understanding of molecular subtypes of gliomas recently led to a revision of the World Health Organization classification criteria for these tumors, introducing the concept of primary and secondary GBMs based on genetic alterations and gene or protein expression profiles. Some of these genetic alterations are currently believed to have clinical significance and are more related to secondary GBMs: TP53 mutations, detectable in the early stages of secondary GBM (found in 65%), isocitrate dehydrogenase 1/2 mutations (50% of secondary GBMs), and also O6-methylguanine-DNA methyltransferase promoter methylation (75% of secondary GBMs).Conclusion From the introduction of the first standard of care (SOC) established in 2005 in patients with a new diagnosis of GBM, a great number of trials have been conducted to improve the actual SOC, but the real turning point has never been achieved or is yet to come. Surgical gross total resection, with at least one more reoperation, radiation therapy plus concomitant and adjuvant temozolomide chemotherapy currently remains the current SOC for patients with GBM.
Keywords: glioblastoma multiforme; prognostic biomarker; genetics; isocitrate dehydrogenase 1/2; O6-methylguanine-DNA methyltransferase (MGMT)